Peningkatan Hasil Belajar Materi Perkalian Melalui Model Kooperatif tipe Teams Games Tournament (TGT) Siswa Kelas IV-A SDN Pakis 1 Surabaya - Nur Maghfiroh; Bekti Wirawati; Nunuk Suliyastuti (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This Classroom Action Research aimed to enhance the mathematics learning outcomes of fourth-grade students at SDN Pakis 01 Surabaya in understanding the multiplication of whole numbers up to 100. The study involved 27 students. Data was collected through observation, tests, and documentation. The cooperative learning model, Teams Games Tournament (TGT), was implemented. Results indicated a significant improvement in students' mathematics achievement, particularly in multiplication, following the implementation of TGT. The percentage of students achieving mastery increased from 37.04% in the pre-cycle to 85.19% in Cycle II. This substantial improvement suggests that TGT effectively created an active, collaborative, and engaging learning environment, motivating students to participate more actively in the learning process. Furthermore, there was a notable increase in the class average across cycles. The implementation of TGT successfully achieved the research objective of enhancing students' understanding of the multiplication concept. Therefore, it is recommended that the TGT model be considered as an alternative to improve the quality of mathematics education in elementary schools.